(3TQGFY GdESdGes - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GdWgGQI, GdWgGQI GSe ddhVhA Ch GdZSd Gh GdJjee Ydi hLg dg (B.. (3aj GSJHGMI GdUdhI hcd hGMO efgG jfbSe Edi hGLH hfOH, aGdhGLH ef GdhVhA eG cGf ddUdGIs
(3BNQgG (B:s
(3BNQgG(B: (3hdh cGf dg CQHY RhLGJ hHfJ aChUi dgeG HeKd fUjH CMOGgf cGfJ GdaQjVI ef GKfjf hKdGKjf ajchf ddRhLGJ GdKef CQHYI Hjfgf HGdShjI hdg Sge (B.. (3hHbj SHYI hYTQjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 123s
(3GdPQjYI, L (B13: 30s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis